Modern Monetary Theory, Fiscal Dominance and the European Central Bank - Aloys Prinz; Hanno Beck (Credit and Capital Markets – Kredit und Kapital, 2022)
In this paper, Modern Monetary Theory (MMT) is confronted with the peculiarities of the institutional setting of the European Monetary Union (EMU) and the monetary policy of the European Central Bank (ECB). Since the financial and euro crises of 2008, monetary policy has changed drastically both in the eurozone and worldwide. With a Quantitative Easing (QE) policy, a new era of monetary policy began that made money available in almost boundless quantities and free of charge. This fits very well with ideas of MMT as it proposes a unification of fiscal and monetary policy in which the government finances its expenditures exclusively with newly created money. Taxes are only used for redistributing income and controlling inflation. Although MMT requires that the government has its own currency, it has been proposed as a policy concept for the EMU. The contribution of this paper to the literature is twofold. Firstly, it is demonstrated that the EMU's institutional setting is not suitable for MMT as the member countries' fiscal sovereignty contradicts the employment of taxation to control inflation. Secondly, MMT's inappropriateness for dealing with banking fragility and financial stability in the EMU is shown. Finally, it is argued that the existence of fiscal dominance in monetary policy is not sufficient for MMT's concept.
Keywords: B52; E52; E53; E63; H63; 330; European Monetary Union; European Central Bank; Modern Monetary Theory; Fiscal Dominance; Feedback Loops